A moving interface finite element formulation for layered structures. (1st July 2016) - Funari, Marco Francesco; Greco, Fabrizio; Lonetti, Paolo
Abstract: A computational formulation based on moving mesh methodology and interface modeling able to simulate debonding mechanisms in multilayered composite beams is proposed. The approach reproduces quasi-static and fast crack propagation in layered structures and, despite existing models available in the literature, a reduced number of finite elements is required to reproduce debonding mechanisms. The theoretical formulation is based on Arbitrary Lagrangian–Eulerian (ALE) methodology and cohesive interface elements, in which weak based moving connections are implemented by using a finite element formulation. In this framework, only the nodes of the computational mesh of the interface region are moved on the basis of the predicted fracture variables, reducing mesh distortions by using continuous rezoning procedures. The use of moving mesh methodology in the proposed model is able to introduce nonlinear interface elements in a small region containing the process zone, reducing the numerical complexities and efforts, typically involved in standard cohesive approach. The analysis is proposed also in a non-stationary crack growth framework, in which the influence of time dependence and the inertial forces are taken into account. In order to verify the accuracy and to validate the proposed methodology, comparisons with existing formulations available from the literature for several cases involving single and multiple debonding mechanisms are proposed. Moreover, a parametric study in terms of mesh sensitivity, robustness and accuracy of the solution is developed.